The expected number of olympic medals: a case study of team Portugal at Tokyo 2020 - Barbosa, Tiago M. (2022)
The 2020 Summer Olympic Games reached to an end in Tokyo, Japan. Even though all the hiccups, constraints, and challenges imposed by the COVID-19 pandemic, the Games were successfully held in August 2021. For the first time in history, Team Portugal won four medals (one gold, one silver, and two bronzes). In 2018 the Portuguese Olympic Committee signed a contract with the Portuguese Institute of Sport and Youth (i.e., Portuguese government) listing the deliverables of the mission Tokyo 2020 against a funding scheme of 18.5 million euros (Contrato n.º 33-A/2018; Contrato — Programa de Desenvolvimento Desportivo n.º CP/1/DDF/2018). The document sets, among other goals and deliverables, that no less than two medals would be won at Tokyo 2020 (section IV.1. of the contract).